Roller –chopping and water infiltration in soils of the western chaco region (Semiárida, 2020)
Roller chopping is widely used in the Chaco region as a means to increase standing forage and accessibility. By modifying vegetation structure, roller-chopping may affect water infiltration in soils, a key attribute of the ecosystem. During 2006-2007 soil water infiltration was assessed using the double ring infiltrometer in four ranches of the western Chaco(EST), in controls and roller-chopped paddocks (TRAT). Data were adjusted to the Kostiakov equation, and the m and k parameters were analyzed using ANOVA with EST and TRAT as independent variables. The coefficient m was not statistically affected, but k was significantly modified by EST (P > F = 0,0001) y EST*TRAT (P > F = 0,0022). Controls showed a larger mean k than the treated paddocks, but in a ranch recently roller-chopped. Results are attributed to the severity and intensity of the roller-chopping and to the post-grazing management, rather than to the mechanical operation itself.
Keywords: Water cycle; Mechanical treatments; Hydrology